Tinjauan Hukum Terhadap Efektivitas Penyidikan Tindak Pidana Pembunuhan Berencana oleh Polres PALI - Ahmad Adinata (Jurnal Hukum Lex Generalis, 2025)
This study examines the investigation of premeditated murder by PALI Police involving Agus Saputra alias Bimo in the death of Juleni. An empirical juridical method was used, based on documents and interviews. The investigation followed legal procedures, including arrest and evidence collection. Article 340 of the Penal Code was fulfilled based on the suspect’s confession and evidence. The study highlights the importance of professionalism and coordination among law enforcement in handling premeditated murder cases